No more ‘Standing the Session’: Gender and the End of Corporate Discipline in the Church of Scotland, c.1890-c.1930 - Brown, Stewart J. (Studies in church history, 1998)
In 1890, the General Assembly of the established Church of Scotland appointed a Commission on the Religious Condition of the People, with instructions to carry out a comprehensive review of the state of religion and morals in the country. The aim was to determine the reasons for non-attendance at church services and for the Church’s declining social influence. The Commission visited the presbyteries, and issued a series of reports between 1891 and 1896. These revealed widespread irreligion, non-attendance, intemperance, and vice. Among the most disturbing revelations, however, were the high levels of illegitimacy in many regions of the country. Sexual immorality, according to the report for the synod of Galloway, in the south west of Scotland, was ‘a rampant sin in the district, and makes a dark blot on the moral life of [the] community’. In the Presbytery of Strathbogie, in the north east, sexual misconduct ‘has so permeated family life, and is so prevalent in the community, that it is difficult to arouse a healthy and vigorous public opinion against it’. The problem seemed to lie in the nature of ecclesiastical discipline within Scottish Presbyterianism. The mode of administering discipline’, the Commission observed in its final report, in May 1896, at present fails to impress the community; it fails to promote repentance in offenders; and it may be asked whether, thus failing, it is not a hindrance rather than a help to the cause of morality. To the more sensitive and delicate in feeling who have yielded to temptation there is a natural repugnance in being obliged to face the minister and elders. … To those who have no such delicacy, the ‘standing of the session’ is little regarded.